2018
DOI: 10.3892/ijmm.2018.3379
|View full text |Cite
|
Sign up to set email alerts
|

High-mobility group protein�B1 silencing promotes susceptibility of retinoblastoma cells to chemotherapeutic drugs through downregulating nuclear factor-κB

Abstract: The aim of the present study was to investigate the effects of high-mobility group protein B1 (HMGB1) silencing on the susceptibility of retinoblastoma (RB) cells to chemotherapeutic drugs and the underlying molecular mechanisms. Western blot analysis revealed that vincristine (VCR), etoposide (ETO) and carboplatin (CBP) significantly increased the expression of HMGB1 in Weri‑Rb-1 and Y79 cells compared with the untreated control (P<0.01). siRNA HMGB1 and siRNA negative control (NC) were transfected to Y79 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…42 HMGB1 increases oncogene activity in the genesis and development of RB, and it is involved in the regulation of RB cell proliferation, autophagy, apoptosis, the cell cycle, viability, metastasis, and chemotherapy sensitivity. [43][44][45][46] In the present study, we demonstrated that miR-665 directly targets HMGB1 and inactivates the Wnt/β-catenin pathway to inhibit the various malignant behaviors of RB in vitro and in vivo. These findings suggest that miR-665-mediated silencing of HMGB1 and inactivation of the Wnt/β-catenin pathway may represent an effective therapeutic approach for patients with RB.…”
Section: Discussionsupporting
confidence: 50%
“…42 HMGB1 increases oncogene activity in the genesis and development of RB, and it is involved in the regulation of RB cell proliferation, autophagy, apoptosis, the cell cycle, viability, metastasis, and chemotherapy sensitivity. [43][44][45][46] In the present study, we demonstrated that miR-665 directly targets HMGB1 and inactivates the Wnt/β-catenin pathway to inhibit the various malignant behaviors of RB in vitro and in vivo. These findings suggest that miR-665-mediated silencing of HMGB1 and inactivation of the Wnt/β-catenin pathway may represent an effective therapeutic approach for patients with RB.…”
Section: Discussionsupporting
confidence: 50%
“…HMGB1 plays a very important role in division and invasion of cancer cells. Therefore, several studies have been performed to inhibit the function of HMGB1 by siRNAs and miRNAs, and all have shown that inhibition of HMGB1 increases the induction of apoptosis and decreases cell division, progression, and invasion of Y79 cells [ 23 , 43 , 44 ]. Limited studies have examined PolA1 in retinoblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…It directly interacts with the two shallow concave surfaces formed by the arms of the HMGB1 box regions [47]. Glycyrrhizin inhibits HMGB1 accumulation in the extracellular space, and prevents its interaction with proinflammatory receptors like TLR4, TLR2, and RAGE receptors [82][83][84][85]. Diseases where inflammation is a major factor in pathogenesis such as oncogenic transformation, bacterial infection, or diet-induced symbiosis are also sensitive to treatment with glycyrrhizin [46,49,52,53].…”
Section: Blocking the Release Of Hmgb1 Using Anti-inflammatory Therap...mentioning
confidence: 99%
“…Histone deacetylases (HDAC) inhibitors are a class of compounds that increase the acetylation of lysine residues on histone proteins by inhibiting the activity of HDAC enzymes. In cancer, HDAC inhibitors inhibit the proliferation of tumor cells in culture and in-vivo by inducing apoptosis and cell cycle arrest [85]. Cellular localization of HMGB1 is dictated by the presence or absence of acetyl groups on the protein.…”
Section: Hdac Inhibitors Increasing Hmgb1 Releasementioning
confidence: 99%